ANALISIS FAKTOR INTERNAL TENAGA KERJA YANG MEMPENGARUHI KECEPATAN DAN KETELITIAN SORTASI BASAH TANAMAN PEGAGAN - Dian Susanti; Devi Safrina (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Gotu Kola (Centella asiatica (L.) Urb) is one of the most popular medicinal plant products in the Indonesian market. The higher the demand for raw materials, the greater the human resources needed. Human resources contain an understanding of the quality and quantity of workers processing simplicia. The wet sorting process is the beginning of the postharvest process which greatly determines the quality of herbal ingredients. This study aims to determine the effect of labor internal factors on the speed and accuracy of the results of sorting wet gotu kola plants. In this study, data collection on workers' internal factors included age, sex, level of education, length of work, and extent of right hand. Workers sort wet gotu kola plants and analyzed in terms of speed and accuracy. The results showed that the area of the right hand labor force had a positive influence and was significantly different from the speed of work. Gender has a negatively significant effect on work speed. The internal factors of labor used in the observation did not have a significant effect on the accuracy of the wet sorting of the gotu kola plant.